PERAN KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU MTSN 1 KOTA MAKASSAR - Sunaryanto, Budi; Khadafi Faizal, Ahmad (JOURNAL J-MPI : JURNAL MANAJEMEN PENDIDIKAN, PENELITIAN DAN KAJIAN KEISLAMAN, 2023)
This study aims to describe the role of the principal in improving teacher performance at MTsN 1 Makassar City which includes several sub-activities. The research approach used is a qualitative approach using field research. Data collection techniques are carried out by observation, interviews, and documentation studies. Data analysis techniques used include data condensation, data presentation, and conclusion/verification. Testing the validity of the data is done through a credibility test that includes triangulation.The results of the study show that, based on the results of data analysis and discussion of the leadership role of the principal in improving teacher performance at MTsN 1 Makassar City, it can be concluded that the principal has carried out his leadership role in improving teacher performance at MTsN 1 Makassar City well. In carrying out his role the principal has adopted a leadership style that is democratic, straightforward and open, prepares time to communicate with school members, emphasizes teachers and school members to be disciplined, and conducts class visits